Teaching the Early Modern Period
XIV, 273 p.
Keywords: This innovative project unites leading scholars of English, History and French to examine the challenges of teaching early modern literature, history and culture within higher education. The volume sets out a variety of approaches to teaching the period and aims to revitalize the connection between teaching and research.